Health complications of female genital mutilation in Sierra Leone - Bjälkander O; Bangura L; Leigh B; Berggren V; Bergström S; Almroth L (Dove Medical Press, 2012)
Owolabi Bjälkander,1 Laurel Bangura,2 Bailah Leigh,3 Vanja Berggren,1 Staffan Bergström,1 Lars Almroth11Division of Global Health, Department of Public Health, Karolinska Institutet, Stockholm, Sweden; 2Inter Africa Committee, Sierra Leone; 3Department of Community Health, College of Medicine and Allied Health Sciences, University of Sierra Leone, Sierra LeoneAbstract: Sierra Leone has one of the highest rates of female genital mutilation (FGM) in the world, and yet little is known about the health consequences of the practice.Purpose: To explore whether and what kind of FGM-related health complications girls and women in Sierra Leone experience, and to elucidate their health care-seeking behaviors.Patients and methods: A feasibility study was conducted to test and refine questionnaires and methods used for this study. Thereafter, a cross-section of girls and women (n = 258) attending antenatal care and Well Women Clinics in Bo Town, Bo District, in the southern region and in Makeni Town, Bombali District, in the northern region of Sierra Leone were randomly selected. Participants answered interview-administrated pretested structured questionnaires with open-ended-questions, administrated by trained female personnel.Results: All respondents had undergone FGM, most between 10 and 14 years of age. Complications were reported by 218 respondents (84.5%), the most common ones being excessive bleeding, delay in or incomplete healing, and tenderness. Fever was significantly more often reported by girls who had undergone FGM before 10 years of age compared with those who had undergone the procedure later. Out of those who reported complications, 187 (85.8%) sought treatment, with 89 of them visiting a traditional healer, 75 a Sowei (traditional circumciser), and 16 a health professional.Conclusion: The high prevalence rate of FGM and the proportion of medical complications show that FGM is a matter for public health concern in Sierra Leone. Girls who undergo FGM before 10 years of age seem to be more vulnerable to serious complications than those who are older at the time of FGM. It is important that health care personnel are aware of, and look for possible complications from FGM, and encourage girls and women to seek medical care for their problems.Keywords: female genital cutting, female circumcision, health consequences, age at FGM, treatment seeking, caregiver